Reevaluating the prognostic value of RAS mutation status in patients with resected liver metastases from colorectal cancer: A systematic review and meta‐analysis. (19th July 2021) - Pikoulis, Emmanouil; Papaconstantinou, Dimitrios; Pikouli, Anastasia; Wang, Jane; Theodoridis, Charalampos; Margonis, Georgios Antonios
Abstract: Background: Although the value of Rat Sarcoma Oncogene (RAS) mutation status in predicting long‐term outcomes in patients with colorectal liver metastases (CRLM) is widely accepted, the magnitude of its impact has recently been challenged by three large cohort studies. The aim of this meta‐analysis is to reevaluate the impact of RAS mutations on overall survival (OS) and disease‐free survival (DFS) in patients who underwent curative‐intent resection of CRLM. Methods: A comprehensive literature search was performed for studies reporting outcomes of patients undergoing curative‐intent surgery stratified by RAS mutation status. Exclusion criteria were defined a priori. Subgroup analysis was performed to evaluate the effect of publication date, sample size, and KRAS vs any RAS mutation on overall outcomes. Results: Ten studies incorporating 3115 patients with known RAS status were identified. Pooled results revealed significantly worse OS (Hazard Ratio 1.5, 95% CI 1.31‐1.71) and DFS (Hazard Ratio 1.36, 95% CI 1.22‐1.52) in RAS‐mutated patients. Subgroup analyses revealed that studies including more than 300 patients or published after 2015 reported lower HR than their counterparts. Conclusion: The results of this meta‐analysis suggest that the prognostic value of RAS mutation status in patients with CRLM has been previously overestimated. Abstract : Highlight Pikoulis and colleagues performed a meta‐analysis of published studies on how RAS mutational status affects patients' overall and disease‐free survival after curative‐intent surgery for colorectal liver metastases. Although RAS mutations significantly impact survival for this particular subset of patients, the prognostic value attributed to RAS status has previously been overestimated.